1993
DOI: 10.1182/blood.v82.2.456.bloodjournal822456
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of an erythropoietin-dependent subline, UT-7/Epo, derived from human leukemia cell line, UT-7

Abstract: UT-7 is a human leukemic cell line capable of growing in interleukin-3 (IL-3), granulocyte/macrophage colony-stimulating factor (GM-CSF), or erythropoietin (Epo) (Komatsu et al, Cancer Res 51:341, 1991). To study the effect of Epo on proliferation and differentiation of UT-7, we maintained the UT-7 cell culture for more than 6 months in the presence of Epo. As a result, a subline, UT-7/Epo, was established. The growth of UT-7/Epo could be supported by Epo but not by GM-CSF or IL-3. UT- 7/Epo showed a greater l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…To test whether EpoR mRNA was present, we isolated total RNA and subsequently performed RT‐PCR using primers to the human sequence of exon 3 and exon 7. As a positive control, we used the Epo‐dependent leukaemia cell line UT‐7, which is known to express the EpoR (Komatsu et al 1993). A fragment of the expected size of 485 bp was observed by agarose gel electrophoresis in both cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether EpoR mRNA was present, we isolated total RNA and subsequently performed RT‐PCR using primers to the human sequence of exon 3 and exon 7. As a positive control, we used the Epo‐dependent leukaemia cell line UT‐7, which is known to express the EpoR (Komatsu et al 1993). A fragment of the expected size of 485 bp was observed by agarose gel electrophoresis in both cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The UT‐7/EPO cell line was maintained in liquid culture with Iscove's Modified Dulbecco's Medium (IMDM; GIBCO Laboratories, Grand Island, NY) supplemented with 10% fetal calf serum (FCS; Hyclone Laboratories, Logan, UT) and EPO (1 U/ml) (Komatsu et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noticing that growth of both original cell lines is not only supported by EPO but also shows dependency on GM‐CSF and IL‐3, both cytokines acting through their receptors constituted by a specific alpha subunit and the common beta subunit. However, when Komatsu et al 24 established the UT‐7/EPO subline, they reported that these cells had lost their response to GM‐CSF and IL‐3 due to a markedly decrease of the common beta subunit expression. Contrarily, TF‐1 cells exhibit complete growth dependency on those cytokines but EPO can only sustain short‐term growth.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro activity of EPO variants was determined by their ability to stimulate proliferation of UT‐7 and TF‐1 erythroid cell lines. 24, 25 Serial 1:2 dilutions of rhEPO or rhNEPO from 4 ng/mL to 0.01 ng/mL (UT‐7 cells) and from 15 ng/mL to 0.06 ng/mL (TF‐1 cells) were placed into culture microtiter plate wells. Cells were harvested from exponentially growing cultures, washed thrice with basal medium and resuspended in assay medium.…”
Section: Methodsmentioning
confidence: 99%